Application of Industrially Relevant HydroFluoroOlefin (HFO) Gases in Organic Syntheses - Varga, Bálint; Csenki, János T.; Tóth, Balázs L.; Béke, Ferenc; Novák, Zoltán; Kotschy, András (Synthesis, 2021)
Hydrofluoroolefin (HFO) gases are state-of-the-art cooling agents with widespread household and industrial applications. Considering their structural benefits these fluorous feedstocks have gained the attention of organic chemists in the last couple of years. In this short review we summarized the existing synthetic transformations of these gaseous starting material and present their applicability in the synthesis of fluorine-containing organic molecules, which have potential importance as building blocks and reagents for diverse syntheses.1 Introduction2 Addition Reactions3 Substitutions4 Organometallic Chemistry4.1 Organolithium Compounds4.2 Organometallic Complexes4.3 Silicon Organic Chemistry4.4 Boron Organic Chemistry4.5 Palladium-Catalyzed Transformations4.6 Metathesis4.7 Hydroesterification, Hydroformylation5 Conclusions
Keywords: HFO; hydrofluoroolefin; fluorine; fluoroalkylation; transition metals